Determinants of Millennial's Continuance Intention for Mobile Banking Services in Johor - Jia Hu Tham; Muhammad Asyraf Hasim; Sallaudin Hassan (Journal of International Business, Economics and Entrepreneurship, 2023)
Mobile banking services usage increasing in recent years, especially during the COVID-19 pandemic. The long-term development of mobile banking depends on the continuous usage of users. Therefore, the purpose of this study was to investigate the determinants that can influence the millennial generation’s continuance intention (CI) to use mobile banking services, including perceived ease of use (PEOU), security (SEC), and trust (TRU). Besides, the researchers also evaluated the level of millennials’ continuance intention for using these services. This study utilised quantitative methods by distributing the online questionnaires in Google form to the millennial users in Johor, Malaysia, by applying convenience sampling. The respondents are millennials born from 1981 until 1996 (between 27 to 42 years old in 2023). Multiple regression analyses were performed to investigate the relationship between the dependent and independent variables. The findings showed that PEOU, SEC, and TRU positively impacted CI and proved that mobile services play significant roles in customer continuance intention in service sectors, and banks are no exception. This study also intended to develop an informative idea for financial institutions to develop and enhance their performance.